Communication strategy of the Geely brand in the Belarusian and Chinese markets - Qi, Xu (Journal of the Belarusian State University. Journalism, 2023)
The communication strategy of the Geely brand in Belarus and China is considered. Its goals are defined (obtaining additional competitive advantages in the domestic and foreign markets, increasing the economic efficiency of production, as well as selling products).